HDL-associated ApoM is anti-apoptotic by delivering sphingosine 1-phosphate to S1P1 & S1P3 receptors on vascular endothelium. Issue 1 (December 2017) - Ruiz, Mario; Okada, Hiromi; Dahlbäck, Björn
Abstract Background High-density Lipoprotein (HDL) attenuates endothelial cell apoptosis induced by different cell-death stimuli such as oxidation or growth factor deprivation. HDL is the main plasma carrier of the bioactive lipid sphingosine 1-phosphate (S1P), which it is a signaling molecule that promotes cell survival in response to several apoptotic stimuli. In HDL, S1P is bound to Apolipoprotein M (ApoM), a Lipocalin that is only present in around 5% of the HDL particles. The goal of this study is to characterize ApoM-bound S1P role in endothelial apoptosis protection and the signaling pathways involved. Methods Human umbilical vein endothelial cells (HUVEC) cultures were switched to serum/grow factor deprivation medium to induce apoptosis and the effect caused by the addition of ApoM and S1P analyzed. Results The addition of HDL+ApoM or recombinant ApoM-bound S1P promoted cell viability and blocked apoptosis, whereas HDL-ApoM had no protective effect. Remarkably, S1P exerted a more potent anti-apoptotic effect when carried by ApoM as compared to albumin, or when added as free molecule. Mechanistically, cooperation between S1P1 and S1P3 was required for the HDL/ApoM/S1P-mediated anti-apoptotic ability. Furthermore, AKT and ERK phosphorylation was also necessary to achieve the anti-apoptotic effect of the HDL/ApoM/S1P complex. Conclusions Altogether, our results indicate that ApoM and S1P are key elements of the anti-apoptotic activity of HDL and promote optimal endothelial function.